The Impact of Cross - Cultural Exchanges on Dual - Cultural Identity: Taking “The Mutual Learning between Chinese Culture and Chinese - Greek Civilizations” as an Example - Guan Chong Li; Yuqin Su; Sijia Jiang; Guodong Zhang (Quality in Sport)
Background: In the context of globalization, cross - cultural communication has become a prominent feature, and , as a symbol of Chinese culture, play an increasingly important role in cross - cultural communication. This study explores the impact of cross - cultural wushu communication on dual cultural identity through the case of Greek students participating in Chinese wushu communication.